Antidepressant Activity of Selective Bioactive Compounds-Diosgenin and Silymarin in an Experimental Animal Model - Sathya. B (Journal of Global Pharma Technology, 2020)
The present study was aimed to investigate the combined effect of bioactive compounds, Diosgenin and Silymarin in an animal model of depression. Wistar albino rats of either sex were randomly divided into five groups and treated for 7 days. Groups I and II were served as a control and a standard and groups III, IV and V were treated with Diosgenin (100 mg/kg, p.o.), Silymarin (100 mg/kg, p.o.) and combination of Diosgenin (50 mg/kg, p.o.) + Silymarin (50 mg/kg, p.o.), respectively. Imipramine (25 mg/kg, p.o.) was used as a standard for all antidepressant models and the activity was screened by using Forced swim test and Tail suspension test. The results suggested that Diosgenin and Silymarin, independently, at a dose of 100 mg/kg, shown anti-depressant like effect with P value less than 0.05 and 0.01, respectively. The compounds when given in combination at a dose of 50 mg/kg, each, shown potentiating antidepressant like activity as compared to their individual effect. It can be concluded that Diosgenin has got a synergistic effect on antidepressant action when given in combination with Silymarin.Keywords: Bioactive compounds, Depression, Diosgenin, Silymarin, Imipramine, Forced swim test, Tail suspension test.